Earthquake Source Characteristics and S-Wave Propagation Attenuation in the Junction of the Northwest Tarim Basin and Kepingtage Fold-and-Thrust Zone - Wang, Hongwei; Wen, Ruizhi (Frontiers in Earth Science, 2020)
We separated the propagation path attenuation and source spectra from the S-wave Fourier amplitude spectra of the observed ground motions recorded during 46 small-to-moderate earthquakes in the junction of the northwest Tarim Basin and Kepingtage fold-and-thrust zone, mainly composed of two Jiashi seismic sequences in 2020 and 2018. Slow seismic wave decay was observed as the distance increased, while the quality factor regressed as 60.066f0.988 for frequency f = 0.254-30 Hz reflects the strong anelastic attenuation in the study region. We estimated the stress drops for the 46 earthquakes under investigation from the preferred corner frequencies and seismic moments by fitting the inverted source spectra and the theoretical ω-square model. The relationship between seismic moment and corner frequency and the dependence of the stress drop on the moment magnitude reveal the breakdown of earthquake self-similar scaling for the events in this study. The temporal variation in stress drops indicates that the mainshock plays a short-term role in the source characteristics for the surrounding earthquakes. Aftershocks immediately following the mainshock show a low stress release and then gradually recover in a short time. The healing process for the fractured fault in the mainshock may be one reason for the stress drop recovery of the aftershock. The foreshock with the low stress release occurring in the high-heterogeneity fault zone may motivate the following occurrence of the largest magnitude mainshock with a high stress drop. We inferred that the foreshock-mainshock behavior, including several moderate events, may be predisposed to occur in our study region characterized by an inhomogeneous crust.